ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERIAN IMUNISASI DASAR LENGKAP PADA BAYI - Ratih Septiana Arpen; Nur Hidayah Afnas (Maternal Child Health Care, 2023)
According to the World Health Organization (WHO), in 2018 there were around 20 millionchildren in the world who did not get complete immunizations. One indicator of the success of thecomplete basic immunization programis the achievement of complete basic immunization (IDL) in Indonesia reaching 87.8% and needs to be increased to reach the target of 93%. The purpose of this study was to determine the factors that influence the provision of complete basic immunization to infants (aged 0-12 months) during the COVID-19 pandemic in the city of Padang in 2021.The research method used mixed methods, quantitative used a cross-sectional approach and qualitative used a phenomenological approach. It was carried out in July-August2021, a sample of 91 people, namely babies at the Ambacang Health Center and Lapai Health Centerin 2021 and 17 informants. Data analysis with Chi Square Test and logistic regression test is to obtain and obtain descriptions, analyzes, interpretation and factors that most influence the Complete Basic Immunization Factors in Infants at Ambacang Health Center and Lapai Health Center Padang City in 2021.Research Results The results of the Chi-Square statistical test on knowledge (0.017), attitude (0.002), mother's perception 0.000), education 0.005), family support (0.020), the role of health workers (0.003), it can be concluded that there is an influence of knowledge, attitude, mother's perception, education, family support, the role of health workers by providing complete basic immunization to infants (aged 0-12 months. Conclusion The most dominant factor influencing complete basic immunization in infants is the mother's perception (p-value 0.000). It is suggested that the Puskesmas can increase the perception of mothers by formulating policies and strategies for health programs, especially those related to the complete basic immunizationprogram for infants in the future.Keywords: Complete Basic Immunization, Covid 19, Knowledge, Education, Attitude, Perception,Family Support, Role of Health Workers